PENENTUAN PENERIMA PINJAMAN KOPERASI MEKAR SURYA KARANGANYAR MENGGUNAKAN METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY OF IDEAL SOLUTION (TOPSIS) - Insania Istiqomah; kustanto kustanto; Bebas Widada (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2019)
ABSTRACTThe problems arise in the form of less objective decision-making and require a long time for selection and there is no computerized system that supports the prioritization of loan recipients. The purpose of this study was to overcome the problem determination of loan recipients by providing objective assessments to prospective loan recipients at the Cooperative Mekar Surya Karanganyar using the TOPSIS method. Loan determination applications use the Visual Basic programming language. Research methods include data collection and analysis and system design. The formulation of this research problem covers how the loan determination at the Cooperative Mekar Surya Karanganyar uses the TOPSIS method and how to build a loan determination application system using the TOPSIS method using the Visual Basic programming language. Based on the test results by comparing the determination of customer loan recipients in the Mekar Surya Cooperative with the calculation of the TOPSIS method proves the application of determining the loan recipient has good performance.Keywords: TOPSIS, Determination of loan recipients, Cooperative